Chemical Constituents from Daphne giraldii Nitsche and Their Contents Simultaneous Determination by HPLC. (14th April 2016) - Huyiligeqi,; Dong, Xiaoxv; Yang, Chunjing; Xu, Guanling; Cao, Sali; Fu, Jing; Lin, Longfei; Ni, Jian
Abstract : Daphne giraldii Nitsche (Thymelaeaceae) is widely distributed in the Chinese provinces of Shaanxi, Gansu, and Qinghai, which has been used in Chinese folk medicine to treat ache and rheumatism. Pharmacologic tests have revealed that the plant has anti-inflammatory, analgesic, and anticancer activities. However, there is still not enough systemic investigation on the chemical constituents and the method for the contents simultaneous determination in D. giraldii . Therefore, the isolation and characterization of the compounds from the stem barks of this plant were reported. Moreover, a facile, accurate, and reliable method has been developed and validated for their simultaneous determination using HPLC-DAD.